Carbon budgets in northern Swedish Forests, 1800-2013 - Stål, Gustav (SLU/Dept. of Forest Ecology and Management, 2018)
Forests and forest management can mitigate increased carbon dioxide (CO2) concentrations in the atmosphere through sequestration of carbon and/or substitution. A major question has been whether it is better to use or conserve forests, with some claiming that European forests carry a huge carbon debt as a result of forestry.